To solve the equation \( 5(x - 1) = 5x - 3 \) by subtracting \( 5x \) from each side, you'll follow these steps:
Starting with the original equation:
\[ 5(x - 1) = 5x - 3 \]
Now, subtract \( 5x \) from both sides:
\[ 5(x - 1) - 5x = 5x - 3 - 5x \]
This simplifies to:
\[ 5(x - 1) - 5x = -3 \]
Now, let’s simplify the left side further:
\[ 5x - 5 - 5x = -3 \]
The \( 5x \) cancels out:
\[ -5 = -3 \]
However, notice that \(-5\) does not equal \(-3\). This indicates that there are no solutions to the original equation.
Thus, after rewriting the equation and simplifying, we find:
\[ -5 \neq -3 \]
This means the first equation has no solution.